Seoul, city of contrasts: masculinity and world capital of makeup for men (2013)
The role of man in society has changed in recent times. This change is evident in South Korea, a country in which culture has been traditionally macho, but that in modernity has welcomed new values and has become a competition scenario, where the strongest survives. There, success is measured not only by qualities and abilities, but also by appearance. This cultural change has transformed Seoul, which is today the world capital of men's makeup.